Leadership Communication as Citizenship : Give Direction to Your Team, Organization, or Community as a Doer, Follower, Guide, Manager, or Leader. - Burtis, John O. O. (SAGE Publications, 2009)
Leadership Communication as Citizenship explains the communication skills you need to help construct effective experiences for an organization, team, or community, whether in the role of doer, follower, guide, manager, or leader. It articulates the important role that communication plays in helping to co-construct group, organizational, or community direction. Effective leadership communication is explored in the context of citizenship, emphasizing the opportunities and responsibilities we each face for helping groups that matter to us, whether a business, a religious institution, or a gove.